Genetic characterization of a cohort with familial parkinsonism and cognitive-behavioral syndrome: A Next Generation Sequencing study. (March 2021) - Picillo, Marina; Ginevrino, Monia; Dati, Giovanna; Scannapieco, Sara; Vallelunga, Annamaria; Siano, Pietro; Volpe, Giampiero; Ceravolo, Roberto; Nicoletti, Valentina; Cicero, Edoardo; Nicoletti, Alessandra; Zappia, Mario; et al.
Abstract: Objective: To perform the genetic characterization of a cohort with familial parkinsonism and cognitive-behavioral syndrome. Methods: A Next Generation Sequencing – based targeted sequencing of 32 genes associated to various neurodegenerative phenotypes, plus a screening for SNCA Copy Number Variations and C9orf72 repeat expansion, was applied in a cohort of 85 Italian patients presenting with parkinsonism and cognitive and/or behavioral syndrome and a positive familial history for any neurodegenerative disorder (i.e., dementia, movement disorders, amyotrophic lateral sclerosis). Results: Through this combined genetic approach, we detected potentially relevant genetic variants in 25.8% of patients with familial parkinsonism and cognitive and/or behavioral syndrome. Peculiar phenotypes are described (Cortico-basal syndrome with APP, Posterior Cortical Atrophy with GBA, Progressive Supranuclear Palsy-like with GRN, Multiple System Atrophy with TARDBP ). The majority of patients presented a rigid-bradykinetic parkinsonian syndrome, while rest tremor was less common. Myoclonic jerks, pyramidal signs, dystonic postures and vertical gaze disturbances were more frequently associated with the presence of a pathogenic variant in one of the tested genes. Conclusions: Given the syndromic approach adopted in our study, we were able to provide a detailed clinical description of patients beyond the boundaries of specific clinical diagnoses and describe peculiar phenotypes. This observation further supports the knowledge that genetic disorders present phenotypic overlaps across different neurodegenerative syndromes, highlighting the limitations of current clinical diagnostic criteria defining sharp boundaries between distinct conditions. Highlights: A genetic panel was applied to 85 patients with parkinsonism and cognitive/behavioral disturbances. Potentially relevant variants were identified in 25% of patients. Peculiar and uncommon clinical phenotypes were described. We were able to provide a clinical description beyond the boundaries of clinical diagnosis. Genetic disorders present phenotypic overlaps across different neurodegenerative syndromes.